Molecular identification and genotyping of Blastocystis sp. in sheep and goats from some areas in Inner Mongolia, Northern China. (June 2023) - Zhang, Junchen; Fu, Yin; Bian, Xiaokun; Han, Han; Dong, Heping; Zhao, Guanghui; Li, Junqiang; Li, Xiaoying; Zhang, Longxian
Abstract: Blastocystis sp. is a kind of unicellular intestinal commensal which is widely distributed in humans and animals, and frequently found in the people who are in close contact with animals. To investigate the prevalence and evaluate the zoonotic potential of Blastocystis sp. in sheep and goats from Inner Mongolia, China, a total of 1037 samples were collected from them, and subjected to nested PCR amplification based on the small subunit ribosomal RNA (SSU rRNA) gene of Blastocystis sp. The sanger sequencing was used for Blastocystis sp. subtype identification. The results indicated that the average infection rate of Blastocystis sp. was 10.70% [95CI: 8.82%–12.58%] (111/1037), including 11.30% [95CI: 7.96%–14.64%] for sheep (39/345) and 10.40% [95CI: 8.13%–12.67%] for goats (72/692). Five Blastocystis subtypes (ST5, ST10, ST14, ST21 and ST26) were identified in the present study. Among them, ST10 was the most dominant subtype in sheep and goats, accounting for 70.27% (78/111) of the total identified positive samples. This is the first report regarding Blastocystis sp. subtypes ST21 and ST26 in goats in China. This study has provided a detail epidemiological data on the prevalence and subtypes distribution of Blastocystis sp. in sheep and goats in Inner Mongolia, China. Our results indicated that sheep and goats could be reservoir host for multiple Bastocystis subtypes, including the zoonotic subtypes. Further studies among humans, livestock and wild animals are needed to better understand their role in the spread of Blastocystis sp. Graphical abstract: Unlabelled Image Highlights: Total of 10.70% were positive for Blastocystis sp. in sheep and goats. Five subtypes of Blastocystis sp. were identified in sheep and goats. Blastocystis sp. ST10 was the predominant genetic variant identified. This is the first report of ST21 and ST26 in goats in China.